The Principle of Economic Justice and Its Implications for Economic Inequality in East Java - Sholeha, Emarotus; Salsabila, Rona; Setianingrum, Nurul; Anggitaningsih, Retna (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
The principle of economic justice plays a crucial role in ensuring the equitable distribution of resources and promoting social and economic welfare. This article explores how the application of economic justice principles can help address economic inequality in East Java Province, focusing on the government's role in reducing regional disparities. Despite East Java’s rapid economic growth, inequalities between urban centers like Surabaya and rural areas such as Madura and Bojonegoro remain significant challenges. Through an in-depth literature review, this study identifies key principles of economic justice, such as the principles of distributional justice, balance, public benefit, and protection, which must be applied to achieve inclusive prosperity. The findings suggest that government efforts through programs like Direct Cash Assistance (BLT), agrarian reform, and the development of sectors such as tourism and local industries are crucial in reducing inequalities. However, the greatest challenges remain in bridging the infrastructure and human resource gaps between cities and rural areas. This study proposes a more coordinated approach between central and regional governments to ensure that the principles of economic justice are effectively implemented across the province, allowing all segments of society to benefit from sustainable economic growth.